Two-Degree Vibration Analysis of a Horizontal Axis Turbine Blade by Finite Differential Methods - Youfeng Zhu; Hongyu Zang; Xiaofei Kong; Peng Ban (Shock and Vibration)
Two-degree vibration partial differential equations of large horizontal axis turbine blades were established by Kallesøe’s model and Greenberg unsteady aerodynamic theory. By means of the finite difference discretization and cantilever beam boundary condition, the equations of blades can be simplified as a general vibration system. Then a linear stationary state space on the system was built. The blade tip vibration in autonomous and nonautonomous system can be simulated by MATLAB vibration toolboxes in time domain. The convergent, flutter, and divergent vibration curves were plotted in the directions of lead-lag and flapping.